(untitled) (Международный научный журнал «Инженер», 2026)
This article presents the results of studies of the process of modifying cotton fabric with fibroin oligomers, the influence of pH, temperature, concentration of polyvalent metal salts, sodium nitrite and resorcinol on the formation of metal complexes in the structure of cotton fiber, as well as the established optimal compositions of the developed powder composite dyes for the production of composite dyes and for dyeing textile cotton and viscose fabrics.